Diplomatic breakthrough in west Asia - Bhardwaj, Atul (Economic and Political Weekly)
Iran and Saudi Arabia, the two arch-rivals of West Asia, have signed a landmark agreement to restore diplomatic ties and reopen embassies after relations were severed in 2016 when Iranian protesters attacked Saudi diplomatic missions in Iran following the Saudi beheading of a Shia spiritual leader Nimr al-Nimr. Previously, Saudi Arabia cut diplomatic ties with Iran after the attacks on its embassy in 1988. The relations were restored in 1991 but tensions continued to persist.- Reproduced